Attending to learners' affective needs: Teachers' knowledge and practices. (December 2020) - Thararuedee, Pariwat; Wette, Rosemary
Abstract: While the importance of both teacher knowledge and affect in successful second language (L2) learning is recognized, relatively little research has explored how teachers draw on their professional knowledge to implement classroom instruction that focuses on learners' affective needs, particularly with regard to the teaching in English in foreign language (EFL) contexts. This study therefore examined why and how four tertiary-level English teachers in Thailand attended to and addressed affective issues in their classrooms. Data collected through observations (OB) and stimulated recall (SR) interviews revealed that teachers took responsibility for meeting learners' affective needs, guided by the principles of promoting English language learning, fostering supportive classroom relations, and cultivating moral values, all of which were found to underpin a variety of classroom practices. It is hoped that gains in our appreciation of the affective dimension of language teaching from this study will contribute to a more complete understanding of second language teaching, and add to existing knowledge on this important topic.